Increases in gonorrhea among high school students following hurricane Katrina. Issue 3 (27th October 2008) - Nsuami, M J; Taylor, S N; Smith, B S; Martin, D H
Abstract : Objective: To determine the prevalence of Neisseria gonorrhoeae in a student population before hurricane Katrina and after their residential neighbourhoods were devastated in the wake of the hurricane. Methods: Students in a New Orleans public high school were offered urine screening for N gonorrhoeae and Chlamydia trachomatis using nucleic acid amplification tests before (n = 346) and after (n = 333) hurricane Katrina. Based on studies showing gonorrhea clustering in physically deteriorated neighbourhoods, it was hypothesised that the post-Katrina gonorrhea prevalence would be higher among students whose neighbourhoods still showed signs of deterioration in the aftermath of the hurricane. Results: Before and after hurricane Katrina, the prevalence of gonorrhea increased from 2.3% (8/346, 95% CI 1.3% to 4.6%) to 5.1% (17/333, 95% CI 3.1% to 8.2%), respectively (one-sided p = 0.027). In logistic regression of gonorrhea controlling for gender, age, chlamydia infection and exposure to hurricane-affected residential neighbourhood conditions, gonorrhea was significantly associated with female gender (odds ratio (OR) 2.6, 95% CI 1.0 to 6.3; p = 0.04) and with chlamydia infection (OR 9.2, 95% CI 3.9 to 21.7; p<0.001). Although of weak statistical significance, there was a strong independent positive trend toward testing positive for gonorrhea after the hurricane (OR 2.2, 95% CI 0.9 to 5.4; p = 0.09). Conclusions: The analysis indicates that the odds of testing positive for gonorrhea more than doubled among students after the hurricane, indicating that surveillance activities should be restored to monitor sexually transmitted infections (STIs) among at-risk populations. Redoubled efforts should be put into STI screening programmes as soon as possible following natural disasters to prevent resurgent STI incidence rates.